2015
DOI: 10.1002/2015gl065152
|View full text |Cite
|
Sign up to set email alerts
|

First MESSENGER orbital observations of Mercury's librations

Abstract: We have coregistered laser altimeter profiles from 3 years of MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) orbital observations with stereo digital terrain models to infer the rotation parameters for the planet Mercury. In particular, we provide the first observations of Mercury's librations from orbit. We have also confirmed available estimates for the orientation of the spin axis and the mean rotation rate of the planet. We find a large libration amplitude of 38.9 ± 1.3 arc sec a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
114
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(146 citation statements)
references
References 39 publications
29
114
3
Order By: Relevance
“…On the basis of theoretical calculations, Mercury is expected to remain close to the Cassini state (Peale 2006). That Mercury is very close to this state has been verified with radar observations, which give an obliquity of 2.04 ± 0.08 arcmin (Margot et al 2007, consistent with analysis of MESSENGER spacecraft gravity data, laser altimetry, and stereo digital terrain models (Mazarico et al 2014;Stark et al 2015). The most recent observations show that the best-fit solutions are offset from the Cassini state by a few arcseconds, but the uncertainty at one standard deviation includes the Cassini state.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…On the basis of theoretical calculations, Mercury is expected to remain close to the Cassini state (Peale 2006). That Mercury is very close to this state has been verified with radar observations, which give an obliquity of 2.04 ± 0.08 arcmin (Margot et al 2007, consistent with analysis of MESSENGER spacecraft gravity data, laser altimetry, and stereo digital terrain models (Mazarico et al 2014;Stark et al 2015). The most recent observations show that the best-fit solutions are offset from the Cassini state by a few arcseconds, but the uncertainty at one standard deviation includes the Cassini state.…”
Section: Introductionsupporting
confidence: 54%
“…It thereby dominates dissipative viscous, topographic, and magnetic effects that would otherwise result in significant displacement of the observable spin axis from the Cassini state position. This result is reassuring as Mercury's spin is observed to occupy the Cassini state (Margot et al 2007Mazarico et al 2014;Stark et al 2015), but at the same time it frustrates the establishment of any constraints on Mercury's interior that could result from a measurable displacement. We show here that the increase in the obliquity from torques exerted by an asymmetric solid inner core can be reversed by the reduction of Mercury's polar moment of inertia from the value inferred if there is no inner core.…”
Section: Introductionmentioning
confidence: 89%
“…Our precision orbit determination methodology The orientation of Mercury's spin axis was earlier determined from Earth-based radar measurements (Margot et al, 2012), a combination of altimeter and imaging data (Stark et al, 2015), and gravity (Mazarico et al, 2014;Verma & Margot, 2016). Our precision orbit determination methodology The orientation of Mercury's spin axis was earlier determined from Earth-based radar measurements (Margot et al, 2012), a combination of altimeter and imaging data (Stark et al, 2015), and gravity (Mazarico et al, 2014;Verma & Margot, 2016).…”
Section: Methods and Geodetic Measurementsmentioning
confidence: 99%
“…Our precision orbit determination methodology The orientation of Mercury's spin axis was earlier determined from Earth-based radar measurements (Margot et al, 2012), a combination of altimeter and imaging data (Stark et al, 2015), and gravity (Mazarico et al, 2014;Verma & Margot, 2016). The uncertainties in the Margot et al (2012), Stark et al (2015), and HgM008 solutions are shown as 95% confidence error ellipses that account for the correlation between and . Mazarico et al (2014) and Verma and Margot (2016) reported only the formal uncertainties of the right ascension and declination of the pole scaled by 10 (red dashed lines).…”
Section: Methods and Geodetic Measurementsmentioning
confidence: 99%
“…For the Love number we adopted the value k 2 = 0.45 measured by MESSENGER [23]. For the rotational parameters we used the following values: the orientation of the rotation axis is defined, in our semi-empirical model, by the arbitrary angles δ 1 = 3 arcmin and δ 2 = 1 arcmin; the amplitudes of the librations in longitude are ε 1 = 38.9 arcsec, as measured by MESSENGER [47], and ε 2 = 40 arcsec [45]. Concerning the relativity parameters, we adopted the GR values for the PN parameters:…”
Section: Simulation Scenario and Assumptionsmentioning
confidence: 99%